Analisis Sistem Transportasi Cerdas Berbasis Big Data dan Cloud Computing - Sri Wiwoho Mudjanarko; Arthur Daniel Limantara; Fauzie Nursandah; Bambang Subiyanto; Hery Lilik Sudarmanto (CAHAYAtech, 2020)
A